Karakteristik Sensori dan Warna Sate Lilit Ayam Dengan Perlakuan Penambahan Gula Kelapa - Shaskara, I Made Ananda Merta; Mertayasa, I Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Satay lilit is a traditional Balinese food that is popular with locals and tourists alike. Satay Lilit is usually made from chicken, beef and pork. Almost all traditional restaurants serve satay lilit as their mainstay menu. The processing of satay lilit is quite complicated with complete spices so that the serving process often takes a long time. Frozen sate lilit, satay lilit that has been cooked, vacuum-packed and frozen, is now being introduced. The shelf life of this satay is relatively long at around 2-3 months. The treatment in this study was the addition of coconut sugar 0%, 5%, 7.5%, 10%, 12.5%, and 15% of the satay dough used. This study aims to determine the effect of coconut sugar addition on the sensory and color characteristics of satay lilit. The second objective was to determine the amount of added sugar to get the best characteristics of satay lilit. The results showed that all treatments of coconut sugar addition had a significant effect on the sensory and color characteristics of satay lilit. The more sugar added, the darker and redder the satay color. The best characteristic of the satay lilit was the addition of 10 percent coconut sugar. This satay lilit has taste characteristics with an average value of 4.6 (slightly sweet to sweet), texture with an average value of 4.45 (normal to slightly hard), overall acceptance with a value of 5.85 (somewhat like to like), then color intensity L of 54.45, a of 2.95 and b of 19.10.